Metallized film for capacitor and preparation process thereof

By introducing nanohybrid dielectric fillers with barium titanate nanoparticles as the core and organic polymer materials as the shell into the polypropylene matrix, a metallized film for capacitors was prepared by RAFT polymerization method, which solved the problem of increasing the dielectric energy storage density of polypropylene-based dielectric materials, and achieved high-performance and miniaturized capacitors.

CN119241954BActive Publication Date: 2025-03-25TONGLING QILI ELECTRONICS MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411783981.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The lower dielectric constant of polypropylene-based dielectric materials limits the further improvement of their dielectric energy storage density and cannot meet the requirements of future capacitors to achieve higher performance and miniaturization.

Method used

A nanohybrid dielectric filler with inorganic barium titanate nanoparticles as the core and organic polymer material as the shell was prepared by reversible addition fracture chain transfer (RAFT) polymerization method, and introduced it into a polypropylene matrix, and molded by hot pressing to prepare a metallized film for capacitors.

Benefits of technology

The relative dielectric constant of the metallized film for capacitors is significantly improved and the dielectric loss is reduced, and the dielectric energy storage density is achieved, which meets the requirements of high performance and miniaturization of capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric films, and discloses a metallized film for capacitors and a preparation process thereof, wherein a chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group is synthesized, and a silanol functional group obtained by hydrolysis reaction of the hydrolysis functional group of the chain transfer agent undergoes a dehydration condensation reaction with a hydroxyl functional group on the surface of a hydroxylated barium titanate nanoparticle, and the chain transfer agent is grafted onto the surface of the barium titanate nanoparticle, and based on a reversible addition-fragmentation chain transfer polymerization method, an azo initiator is used to initiate an olefin monomer to carry out in-situ reversible addition-fragmentation transfer polymerization on the surface of the barium titanate nanoparticle, and an organic polymer chain is grafted onto the surface of the barium titanate nanoparticle by a covalent bond method, and a nano-hybrid dielectric filler is obtained, which is introduced into a polypropylene matrix, and is pressed and formed by a hot pressing method to obtain a metallized film for capacitors. The invention achieves a beneficial technical effect of significantly suppressing the dielectric loss of the metallized film for capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dielectric films, in particular to a metallized film for capacitors and a preparation process thereof. Background Art

[0002] With the continuous development of the electronics, communications and energy fields, their devices are constantly evolving towards high performance, miniaturization and low latency, which puts higher and higher requirements on the dielectric properties of materials. Polymer dielectric materials, especially polypropylene (PP) materials, have significant advantages such as low dielectric loss, high breakdown strength, excellent processability and low cost, and have broad application prospects in energy storage capacitors and 5G communications. In the field of film capacitors, biaxially oriented polypropylene film (BOPP) is currently the preferred material for various commercial dry capacitors and wet capacitors, and is widely used in electric vehicles and high-voltage power transmission and transformation.

[0003] Although PP-based dielectric materials have been widely used, the low dielectric constant of PP limits the further improvement of its dielectric energy storage density and cannot meet the requirements of high performance and miniaturization of future capacitors.

[0004] Introducing high dielectric constant fillers to prepare PP-based composites is a simple and effective strategy, but adding nanoparticles to polymers will increase leakage current. In addition, when inorganic fillers are introduced into polymers, due to the large difference in surface energy between the two and the weak interaction force, the density of polymer chains near the interface will decrease, the free volume will increase, and charges will migrate more easily. Summary of the invention

[0005] The invention provides a preparation process of a metallized film for a capacitor. A nano-hybrid dielectric filler with inorganic barium titanate nanoparticles as a core and an organic polymer material as a shell is prepared by using a reversible addition fragmentation chain transfer (RAFT) polymerization method. The nano-hybrid dielectric filler is introduced into a polypropylene matrix to prepare a metallized film for a capacitor having excellent dielectric properties.

[0006] A metallized film for capacitors, comprising the following raw materials in parts by weight:

[0007] 100 parts of polypropylene resin;

[0008] 1-10 parts of compatibilizer;

[0009] 0.1-0.5 parts of antioxidant;

[0010] 3-15 parts of nano hybrid dielectric filler;

[0011] Among them, the nano-hybrid dielectric filler is based on the reversible addition-fragmentation chain transfer polymerization method. A chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group is grafted onto the surface of hydroxylated barium titanate nanoparticles. The olefin monomer is initiated by an azo initiator to undergo in-situ reversible addition-fragmentation transfer polymerization on the surface of the barium titanate nanoparticles, and the organic polymer chain is grafted onto the surface of the barium titanate nanoparticles by a covalent bond.

[0012] Preferably, the vinyl monomer is one of 2-methoxyethyl acrylate, methyl methacrylate and styrene.

[0013] Preferably, the compatibilizer is one of polypropylene grafted maleic anhydride PP-g-MAH, silane grafted polypropylene VTMS-g-PP, and maleic anhydride / silane grafted polypropylene MAH / VTMS-g-PP.

[0014] Preferably, the antioxidant is antioxidant 1010 or antioxidant 1076.

[0015] Preferably, the average size of the barium titanate nanoparticles used in the hydroxylated barium titanate nanoparticles is 100-200 nm.

[0016] A preparation process of a metallized film for capacitors comprises the following steps: melt-blending a nano-hybrid dielectric filler, a compatibilizer, an antioxidant and polypropylene powder, and pressing the mixture at a temperature of 180-220°C, a pressure of 10-20MPa and a time of 10-30min to obtain a metallized film for capacitors with a thickness of 1-2mm.

[0017] Preferably, the preparation method of the nano-hybrid dielectric filler is:

[0018] Step S1, 1 molar equivalent of silane coupling agent KH-540 and 2.01-2.1 molar equivalents of hydroxyethyl methacrylate undergo amine-ene addition reaction to obtain a dihydroxy monomer;

[0019] Step S2, under the catalytic effect of concentrated sulfuric acid, 1 molar equivalent of the dihydroxy monomer and 2.05-2.25 molar equivalents of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid undergo an esterification reaction to obtain a chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group;

[0020] Step S3, the hydrolyzed functional groups of the chain transfer agent synthesized in step S2 undergo a dehydration condensation reaction to obtain the silanol functional groups and the hydroxyl functional groups on the surface of the hydroxylated barium titanate nanoparticles, so as to graft the chain transfer agent containing the dual non-polar long alkyl chain groups onto the surface of the barium titanate nanoparticles, thereby obtaining barium titanate nanoparticles with the chain transfer agent containing the dual non-polar long alkyl chain groups grafted on the surface;

[0021] Step S4, under the initiation of an azo initiator, in situ initiates the reversible addition-fragmentation transfer polymerization of olefin monomers on the surface of the barium titanate nanoparticles, and covalently grafts the organic polymer chains to the surface of the barium titanate nanoparticles to obtain a nano-hybrid dielectric filler.

[0022] Preferably, the mass ratio of the hydroxylated barium titanate nanoparticles to the chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group is 1:(0.2-0.8);

[0023] Preferably, the mass ratio of the barium titanate nanoparticles with the chain transfer agent containing a double non-polar long alkyl chain group grafted on the surface to the olefin monomer is 1:(3-7).

[0024] Preferably, the azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.

[0025] Compared with the prior art, the present invention has the following beneficial technical effects:

[0026] A chain transfer agent containing two nonpolar long alkyl chain groups and a hydrolyzable functional group was synthesized;

[0027] On the one hand, the chain transfer agent undergoes a dehydration condensation reaction with the hydroxyl functional groups on the surface of the hydroxylated barium titanate nanoparticles, and the chain transfer agent containing a double non-polar long alkyl chain group is grafted onto the surface of the barium titanate nanoparticles. Based on the reversible addition-fragmentation chain transfer (RAFT) polymerization method, under the initiation of an azo initiator, the reversible addition-fragmentation transfer polymerization of olefin monomers is in situ initiated on the surface of the barium titanate nanoparticles, and the organic polymer chain is grafted onto the surface of the barium titanate nanoparticles by a covalent bond method, thereby obtaining a nano-hybrid dielectric filler.

[0028] Compared with the modification of the surface of barium titanate nanoparticles by using small molecule coupling agents, although the dispersibility of barium titanate nanoparticles can be improved, a complete coating layer cannot be formed. On the other hand, an organic polymer shell layer is coated on the surface of barium titanate nanoparticles, and each polymer chain is connected to the surface of barium titanate nanoparticles, which greatly increases the polymer chain density on the surface of barium titanate nanoparticles, reduces the free volume, and limits the charge migration on the surface of barium titanate, which can effectively reduce leakage current and reduce losses.

[0029] On the other hand, the chain transfer agent grafted on the surface of the barium titanate nanoparticles utilizes two non-polar long alkyl chain groups to be physically entangled with the non-polar polypropylene matrix, thereby improving the compatibility of the barium titanate nanoparticles with the polypropylene matrix.

[0030] The nano-hybrid dielectric filler is introduced into the polypropylene matrix and pressed by hot pressing to obtain a metallized film for capacitors.

[0031] At test frequency 10 2 Hz-10 5 At Hz, the relative dielectric constant of the metallized film for capacitors was tested to be 19.7-22.3 and the dielectric loss was 0.0007-0.0029;

[0032] The invention achieves the beneficial technical effect of significantly suppressing the dielectric loss of the metallized film for capacitors. DETAILED DESCRIPTION Embodiment 1:

[0033] The chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group is synthesized, and the synthesis process is as follows:

[0034] Process I: 1 molar equivalent of silane coupling agent KH-540 (3-aminopropyltrimethoxysilane) and 2.09 molar equivalents of hydroxyethyl methacrylate undergo amine-ene addition reaction to obtain a dihydroxy monomer, the chemical structure of which is:

[0035] ;

[0036] The experimental steps for synthesizing the dihydroxy monomer are as follows: 2 mL of silane coupling agent KH-540, 2.8 mL of hydroxyethyl methacrylate and 25 mL of anhydrous ethanol are added into a three-necked flask, stirred and reacted for 12 h under reflux, and the solvent and unreacted hydroxyethyl methacrylate are evaporated by a rotary evaporator to obtain the dihydroxy monomer;

[0037] Process II: Under the catalytic action of concentrated sulfuric acid, 1 molar equivalent of dihydroxy monomer and 2.2 molar equivalents of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid undergo esterification reaction to obtain a chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group, and its chemical structure is:

[0038] ;

[0039] The experimental steps for synthesizing a chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group are as follows: 4.39 g of a dihydroxy monomer, 8 g of 2-[dodecylthio(thiocarbonyl)thio]-2-methylpropionic acid, 0.15 mL of concentrated sulfuric acid and 80 mL of N,N-dimethylformamide are added to a three-necked flask, cyclohexane is used as a water-carrying agent, and the mixture is stirred and reacted at 122° C. for 6 h, cooled to room temperature, poured into deionized water, filtered, neutralized with a saturated sodium bicarbonate solution to a pH value of 7, washed with deionized water, and dried over anhydrous sodium sulfate to obtain a chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group;

[0040] The hydrogen spectrum characterization results of the chain transfer agent containing double non-polar long alkyl chain groups and hydrolysis functional groups are as follows: 1H NMR (400MHz, DMSO-d6, δ, ppm): 0.62-0.78 (m, 2H), 0.86-0.92 (t, 6H), 1.15-1.16 (d, 6H), 1.19-1.46 (m, 36H), 1.52-1.64 (m, 2H), 1.67-1.77(m, 16H), 2.47-2.63(m, 4H), 2.66-2.71(m, 2H), 2.93-2.98(m, 2H), 3.13-3.29(m, 4H), 3.57(s, 9H), 4.25-4.47(m, 8H). Embodiment 2:

[0041] Preparation of hydroxylated barium titanate nanoparticles: 10 g of barium titanate particles (barium titanate BaTiO3, average size of 100 nm) and 60 mL of hydrogen peroxide (30 wt %) were added to a flask, ultrasonically dispersed for 1 h, refluxed at 105 ° C for 4 h, centrifuged at 9000 rpm for 10 min, washed with deionized water, and vacuum dried at 80 ° C for 12 h to obtain hydroxylated barium titanate nanoparticles. Embodiment 3:

[0042] Chain transfer agent grafted on the surface of barium titanate nanoparticles: 10 g of hydroxylated barium titanate nanoparticles prepared in Example 2 and 80 mL of anhydrous toluene were added to a flask, and ultrasonically dispersed for 1 hour. 5 g of the chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group prepared in Example 1 was added, and nitrogen was passed through. The mixture was refluxed at 80°C for 24 hours, centrifuged at 9000 rpm for 10 minutes, washed with anhydrous toluene, and vacuum dried at 80°C for 12 hours to obtain barium titanate nanoparticles with a chain transfer agent grafted on the surface. Embodiment 4:

[0043] Preparation of poly (2-methoxyethyl 2-acrylate)-coated barium titanate nanoparticles with a core-shell structure: 2 g of the barium titanate nanoparticles with a surface grafted chain transfer agent prepared in Example 3 and 50 mL of N,N-dimethylformamide were added to a flask, ultrasonically dispersed for 1 hour, 10 mL of 2-methoxyethyl 2-acrylate was added, nitrogen was passed through, the temperature was raised to 70°C, 15 mg of azobisisobutyronitrile was added, the polymerization reaction was carried out at 70°C for 24 hours, the mixture was centrifuged at 9000 rpm for 10 minutes, precipitated with methanol, and vacuum dried at 80°C for 12 hours to obtain a nano-hybrid dielectric filler. Embodiment 5:

[0044] Preparation of polypropylene resin: polypropylene pellets (purchased from Shanghai Tingyuan Plastic Technology Co., Ltd., brand HJ730) were dissolved in xylene solution at a mass ratio of 1:40, stirred at a constant temperature of 160°C for 3 hours, filtered and dried in a vacuum drying oven at 70°C for 6 hours to obtain polypropylene resin;

[0045] Preparation of a metallized film for capacitors: The nano-hybrid dielectric filler prepared in Example 4, the compatibilizer polypropylene grafted maleic anhydride (PP-g-MAH), the antioxidant 1010 and the polypropylene resin were melt-blended at 190° C. and 60 rpm for 10 min, and the mixture was pressed by hot pressing at a temperature of 190° C., a pressure of 15 MPa and a time of 30 min to obtain a metallized film for capacitors with a thickness of about 1.5 mm;

[0046] The amount of nano hybrid dielectric filler is 8% of the amount of polypropylene resin, the amount of polypropylene grafted maleic anhydride (PP-g-MAH) is 5% of the amount of polypropylene resin, and the amount of antioxidant 1010 is 0.3% of the amount of polypropylene resin. Embodiment 6:

[0047] Dielectric performance test: The dielectric loss and capacitance C of the metallized film sample for capacitor prepared in Example 5 (silver electrode was sputtered on the sample surface by magnetron ion sputtering) were tested by dielectric spectrum analyzer, and the test frequency was 100 Hz-1 MHz;

[0048] According to the capacitance C, the relative dielectric constant ε of the sample is calculated by the following formula (1):

[0049] ε=(C×d)÷(ε0×A) (1)

[0050] Where: C represents capacitance, unit is F;

[0051] d represents the thickness of the sample, in m;

[0052] A represents the surface area of ​​the sample, in m 2 ;

[0053] ε0 represents the dielectric constant of vacuum, ε0=8.854×10 -12 F / m;

[0054] The above test results are shown in Table 1 below;

[0055] Table 1 Experimental results of dielectric properties of metallized films for capacitors

[0056]

[0057] Note: At test frequency 10 2 Hz-10 5 At Hz, the relative dielectric constant of pure polypropylene film was tested to be 1.86-1.88 and the dielectric loss was 0.00014-0.00029;

[0058] At test frequency 10 2 Hz-10 5At Hz, the dielectric constant of the barium titanate / polypropylene composite film was tested to be 15.9-18.2 and the dielectric loss was 0.013-0.057;

[0059] The difference between the pure polypropylene film and the metallized film for capacitors in Example 5 is that no nano-hybrid dielectric filler is added;

[0060] The difference between the barium titanate / polypropylene composite film and the metallized film for capacitors in Example 5 is that directly purchased raw barium titanate particles (barium titanate BaTiO3, with an average size of 100 nm) are used to replace the nano-hybrid dielectric filler.

[0061] The experimental results show that the dielectric modification of polypropylene substrate using nano-hybrid dielectric fillers can effectively improve the dielectric constant of the polypropylene substrate while playing a technical role in significantly suppressing the dielectric loss of metallized films used in capacitors.

Claims

1. A metallized film for capacitors, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polypropylene resin; 1-10 parts of compatibilizer; 0.1-0.5 parts of antioxidant; 3-15 parts of nano hybrid dielectric filler; Among them, the nano-hybrid dielectric filler is based on the reversible addition-fragmentation chain transfer polymerization method, in which a chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group is grafted onto the surface of hydroxylated barium titanate nanoparticles, and an azo initiator initiates an in-situ reversible addition-fragmentation chain transfer polymerization of olefin monomers on the surface of barium titanate nanoparticles, and the organic polymer chain is grafted onto the surface of barium titanate nanoparticles by a covalent bond method. The chemical structure of the chain transfer agent containing a double non-polar long alkyl chain group and a hydrolysis functional group is: 。 2. The metallized film for capacitor according to claim 1, characterized in that: The vinyl monomer is one of 2-methoxyethyl acrylate, methyl methacrylate and styrene.

3. The metallized film for capacitor according to claim 1, characterized in that: The compatibilizer is one of polypropylene grafted maleic anhydride PP-g-MAH, silane grafted polypropylene VTMS-g-PP, and maleic anhydride / silane grafted polypropylene MAH / VTMS-g-PP.

4. The metallized film for capacitor according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 1076.

5. The metallized film for capacitor according to claim 1, characterized in that: The average size of the barium titanate nanoparticles used in the hydroxylated barium titanate nanoparticles is 100-200 nm.

6. A process for preparing a metallized film for capacitors according to any one of claims 1 to 5, characterized in that: The preparation process is as follows: melt-blending nano hybrid dielectric filler, compatibilizer, antioxidant and polypropylene resin powder, and pressing the mixture at a temperature of 180-220° C., a pressure of 10-20 MPa and a time of 10-30 min to obtain a metallized film for capacitors with a thickness of 1-2 mm.

Citation Information

Patent Citations

  • Modified polypropylene film, preparation method and application in capacitor

    CN119019725A